Budapest és a modernizáció kihívásai - Beluszky, Pál (Tér és Társadalom, 1992)
The study summarizes the characteristic features of the society of the capital city of Hungary, Budapest, in the transformation period, the suitability of the society for modernization, the conflicts resulting from the modernization process, and the conflicts taking place in the urban structure and the urban land use resulting from the spread of market economy. The society of Budapest has been a very specific phenomenon in Hungary since the mid-19th century, namely the acceleration of the development of bourgeois society and economy. After the so-called Compromise (1867 – the compromize agreement between the Habsburg dinasty and the Hungarian political factors on the parital re-establishment of national selfdetermination, and the establishment of dual monarchy), the previously limited conditions for economic growth and bourgeois development had become highly favourable. The last third of the 19th century and the years around the turn of the century resulted in the most dynamic economic development of the country. Budapest had a very special role in this modernization process: the capital city became the bridge-head of technical civilization, the institutions of capital development, the innovations, the new artistic movements and social ideas, and – last but not least – of the domestic and foreign capital. The position of Budapest was strengthened by the national intentions which aimed at turning Budapest into an „equal" partner of Vienna. The population of Budapest, which had become a real city by the turn of the century, had been increasing rapidly (187 thousand in 1857, 716 thousand in 1900, and close to 1 million in 1914). The above specific situation was reflected in the society of the capital city as well, as it was 9 unique formation in the country. The characteristic features of this society were the following: Being different: Budapest was the only place in the whole country where the civil, bourgeois society developed completely: the population of the capital city was decisively of foreign origin (in 1870, only 46% of her population had Hungarian as mothertongue). Irregular structure: the society of Budapest differed from the mature societies of the European capital cities. The most striking differences were the small number and economic and political weakness of the middle social strata , the poverty of the petit bourgeoisie, and their little chance to get into the middle class. (This is very well reflected, for example, in the housing stock of Budapest: the proportion of the flats with one room was 54,7% in 1911.) In this period, the elements of „market" (class) and feudal organizations co-existed in the society of the capital city. The attempt of Budapest to join up the West came to a sudden stop as a result of the First World War. As a consequence of the peace treaties ending the War, the situation of Budapest changed fundamentally, whereas the structure of the society stayed to be almost the same. The geopolitical changes taking place after the Second World War fundamentally changed the position of Budapest: Hungary became the periphery of the Soviet Union. Her position was determined by the conditions granted by the socialist order (dictatorship in the society and in economic management, termination of private ownership, forced economic development, lack of capital, etatism. etc.). However, the position of Budapest stayed to be favourable inside the country: the concentration of the material and intellectual resources continued to exist. As a power-centre, the capital city enjoyed the advantages of extensive redistribution. The society of Budapest became more homogenous after 1948. The ownership, property and power basis of the previous social structure ceased to exist. Almost all the citizens of the capital city became civil servants. The declared egalitarian ideas of socialism, especially until 1956; exerted considerable influence on social practice. During the decades of the so-called Kádárconsolidation (after 1963-1964), the state facilitated certainlimited, individual ways of enrichment. The majority of them, however, were related to the second economy. These were exactly the ideological, political and legal acknowledgement, and the spread of the different forms of the second economy which shaped the special situation of Hungary within the countries of the Soviet block. In the early 1980s, the proportion of the families participating in the second economy was 64-65 % in Budapest. Relationship with the first and the second economies, or – in other words – with the civil and market formations, was not separated at personal, and even less at family levels. The above model of social structure is in transition these days. Gradual separation of the two different princíples of organization, and the spread of market organizations are the most striking features of this process. The market sector intself also has two different sides: it is growing rapidly in the first economy, but also continues to exist as a second economy. In 1992, one-fifth of the active earners worked in the first economy. The society of Budapest is also Janus-faced: As certain elements of market organization continued to exist during the socialism as well (mostly limited within the frameworks of the second economy), and as certaion petit-bourgeois-type of social changes continuously took place, this society is suitable for and open to modernization and bourgeois development in many respects. On the other hand, however, the society's conditions, knowledge, reactions, etc. are also hinderous factors, and put up a limit to this development, making the bourgeois development a long process this way. The modernization of the society of Budapest also results in several conflicts: extensive, „non-market inclusions" continue to exist , and these are also reflected in spatial terms (development of slums and ghettoes). During the period following the political transformation, the changes in the property and ownership relations exert the biggest influence in terms of the urban structure; the regulatory mechanisms of the real-estate market have regained their significance. This forces out the spread of functions which are characteristic of the words „location" or „place".The process of city development gained new impetus, and the city is growing primarly in horizontal direction. However, this is partly a spatial process; the city, in narrow terms, primarily grows Southwards, partly in the revitalized sidestreets, and finally in the cellars, and courtyards. The value of the end of the city had been upgraded due to the extremely high real estate prices of the city centre (this is further promoted by the construction of the new highway that will avoid the city). Segregation is increasing. The „socialist" characteristics of segregation were the result of the fact that this primarily meant the move of the better-to-do into the parts of the city with higher social prestige. At the same time, the concentration of „poverty" was kept under control exactly by low rents and low maintenance and utility costs. All these resulted in the fact that the zones of poverty did not so much develop by the mobility lines, but much more by the autochtomous deterioration of the housing stock and the neighbourhood.